ALASAN PEMAAF TERHADAP PERBUATAN PENIPUAN PADA KONTRAK KERJASAMA PT. MARINDO JAYA SEJAHTERA DAN PT HELLICARG INDONESIA - Lubis, Ivan Ghani; Mulyadi, Mahmud; Trisna, Wessy (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: In certain situations, if an act is proven not to constitute a criminal act, this means that the act charged and proven is not regulated and does not fall within the scope of criminal law. The formulation of the problem in this thesis research is what is the point of contact between the crime of fraud and the crime of embezzlement and acts against civil law in the legal system in Indonesia, what is the basis for judges' considerations in deciding criminal cases using forgiving reasons due to the influence of coercive power, how is the application of reasons for expunging crimes in the judge's decision in the case between PT. Marindo Jaya Sejahtera and PT Hellicarg Indonesia. The research method used is a normative legal research method with descriptive analytical research characteristics, with primary, secondary and tertiary data sources, with a statutory approach (status approach) and a conceptual approach (conceptual approach). This research data analysis is qualitative analysis. The point of contact between the crime of fraud, the crime of embezzlement and acts against civil law in the legal system in Indonesia is the elements of the act itself. Keyword: Fraud, Embezzlement, Forgiving Reasons, Justifying Reasons Abstrak: Situasi tertentu, apabila suatu perbuatan terbukti tidak merupakan tindak pidana yang artinya, perbuatan yang didakwakan dan yang telah terbukti tadi tidak ada diatur dan tidak termasuk ruang lingkup hukum pidana. Rumusan masalah dalam penelitian tesis ini adalah bagaimana titik singgung keterkaitan antara pidana penipuan dengan pidana penggelapan dan perbuatan melawan hukum perdata dalam sistem hukum di Indonesia, apa dasar pertimbangan hakim dalam memutus perkara pidana menggunakan alasan pemaaf karena pengaruh daya paksa, Bagaimana penerapan alasan penghapus pidana pada putusan hakim dalam perkara antara PT. Marindo Jaya Sejahtera dan PT Hellicarg Indonesia. Metode penelitian yang digunakan adalah metode penelitian hukum normatif dengan sifat penelitian deskriptif analisis, dengan sumber data primer, sekunder dan tersier, dengan pendekatan perundang-undangan (statuste approach) dan pendekatan konseptual (conceptual approach). Analisis data penelitian ini adalah analisis kualitatif. Titik singgung keterkaitan antara pidana penipuan dengan pidana penggelapan dan perbuatan melawan hukum perdata dalam sistem hukum di Indonesia adalah pada unsur-unsur perbuatan itu sendiri. Kata Kunci: Penipuan, Penggelapan, Alasan Pemaaf, Alasan Pembenar